2010
DOI: 10.1007/s10554-010-9677-1
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of long-term reverse left ventricular remodeling after revascularization or medical treatment in patients with ischemic cardiomyopathy: a comparative study between SPECT and MRI

Abstract: Patients with ischemic heart disease and depressed left ventricular (LV) ejection fraction (LVEF) develop varying degrees of LV remodeling after cardiac surgical revascularization. Fifty-three patients with stable ischemic heart disease and impaired LV function (LVEF 34.9 ± 4%) were prospectively followed up for 24 months. Thirty-seven patients underwent coronary artery bypass grafting (CABG), 16 patients were treated conservatively. Cardiac magnetic resonance imaging (MRI) and SPECT were performed at baseline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
(71 reference statements)
0
10
0
1
Order By: Relevance
“…The key conclusions of this study can be formulated as follows: 1) a cut-off value of -5.3% for speckle tracking derived parameter SL Smax identified segments with nonviable myocardium presence (DE >75%) on ceCMR with a 83.1% sensitivity and 84.8% specificity; 2) the cut-off values SL Smax , which increase accuracy of the model predicting an occurrence of non-viable myocardium even more, can be derived for perfusion territories of individual coronary arteries corresponding approximately to the region of the LV frontal, lateral, and inferior myocardial wall; 3) as compared to the rest perfusion myocardial SPECT, 2 Proportion of segments with given endpoint in analyzed group of segments 3 Area under curve based on ROC analysis supplemented by its 95% confidence interval 4 Statistical significance of AUC 5 Optimal cut off of SL Smax with the best combination of sensitivity and specificity 6 Sensitivity and specificity at optimal cut off 2 Odds ratio for univariate and multivariate models based on logistic regression; multivariate regression based on forward stepwise selection algorithm 3 Only two Q REST categories, which were most significant in univariate model, are chosen into the multivariate model 4 Cut-off for SL Smax is used from previous table; patients above given cut-off are taken as "risk" group in the analysis (despite the value of OR for given endpoint) 5 Multivariate regression model using different SL Smax cut-offs the myocardium deformation analysis is more accurate in predicting LV non-viable myocardium, which is evident on the result obtained in the area of the inferior wall corresponding to the RCA myocardium perfusion territory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The key conclusions of this study can be formulated as follows: 1) a cut-off value of -5.3% for speckle tracking derived parameter SL Smax identified segments with nonviable myocardium presence (DE >75%) on ceCMR with a 83.1% sensitivity and 84.8% specificity; 2) the cut-off values SL Smax , which increase accuracy of the model predicting an occurrence of non-viable myocardium even more, can be derived for perfusion territories of individual coronary arteries corresponding approximately to the region of the LV frontal, lateral, and inferior myocardial wall; 3) as compared to the rest perfusion myocardial SPECT, 2 Proportion of segments with given endpoint in analyzed group of segments 3 Area under curve based on ROC analysis supplemented by its 95% confidence interval 4 Statistical significance of AUC 5 Optimal cut off of SL Smax with the best combination of sensitivity and specificity 6 Sensitivity and specificity at optimal cut off 2 Odds ratio for univariate and multivariate models based on logistic regression; multivariate regression based on forward stepwise selection algorithm 3 Only two Q REST categories, which were most significant in univariate model, are chosen into the multivariate model 4 Cut-off for SL Smax is used from previous table; patients above given cut-off are taken as "risk" group in the analysis (despite the value of OR for given endpoint) 5 Multivariate regression model using different SL Smax cut-offs the myocardium deformation analysis is more accurate in predicting LV non-viable myocardium, which is evident on the result obtained in the area of the inferior wall corresponding to the RCA myocardium perfusion territory.…”
Section: Discussionmentioning
confidence: 99%
“…Single photon emission computed tomography (SPECT) is considered to be a powerful predictor of myocardial viability 5 . CeCMR based parameters of segmental scar transmurality have greater accuracy in predicting reverse LV remodeling than rest SPECT results in predicting long term LV reverse remodeling and LV ejection fraction improvement after surgical revascularization 6 . Speckle tracking echocardiography (STE) has become a simple, rapid, relatively accurate and angle-independent echocardiographic method to assess and quantify regional myocardial function based on tracking of specific speckle patterns created by interference of ultrasound beams in the myocardium.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, among a cohort of 50 CAD patients undergoing elective coronary revascularization, Kim et al showed that dysfunctional but viable myocardium on pre-procedural DE-CMR predicted post-revascularization recovery of LV function (61). Other studies have shown viability assessment via DE-CMR to predict reduction in LV chamber size among patients undergoing elective coronary bypass graft surgery, as well as among patients undergoing PCI (60,62,63). Of interest, absence of viable myocardium within the mitral apparatus has been shown to stratify likelihood of MR following acute MI, suggesting this approach may predict longitudinal risk for MR in post-MI patients being considered for coronary revascularization (21).…”
Section: Prediction and Monitoring Of Mr Therapeutic Responsementioning
confidence: 99%
“…Skala et al [43] directly compared myocardial perfusion SPECT and cardiac MRI to predict improvement of LVEF 24 months after CABG. They prospectively enrolled 53 patients with stable ischemic heart disease and mean LVEF of 35 %, of which 37 patients underwent CABG.…”
Section: Nuclear Cardiologymentioning
confidence: 99%